Ethics And Legal Issues In Online Counseling Services: Counseling Principles Analysis - Zadrian Ardi; M. Rido Mulia Putra; Ifdil Ifdil (Jurnal Psikologi Pendidikan dan Konseling: Jurnal Kajian Psikologi Pendidikan dan Bimbingan Konseling, 2017)
Challenges of living and dynamics modern society has spawned complex problems experienced by individuals. Counseling process with a variety formats attempt to develop the optimization of the individual. The development of the counseling process format formed a variety of alternative media that are capable to accommodating the communication process between the counselor and the client. The Media creates an atmosphere of counseling in long-distance (distance) condition has some advantages as well as disadvantages. One of the distance counseling forms is counseling online. With one form of service with fairly new developments, online counseling has had a significant positive impact on easing the client's problems. But on the other hand, this service also has some weaknesses that must be understood and controlled, especially for a counselor. This manuscript uses a documentary study approach on ethical conditions, counseling issues in Indonesia and discusses some of the ethical issues that must be understood by counselors during the process of online counseling in keeping some of the important principles in the counseling process.